FDG PET to Diagnose Neurolymphomatosis in a Case of Triple-Hit B-Cell Lymphoma - Bund, Caroline; Heimburger, Céline; Trensz, Philippe; Fohrer, Cécile; Kremer, Stéphane; Namer, Izzie-Jacques (Clinical nuclear medicine, 2017)
A 46-year-old man with stage IV triple-hit B-cell lymphoma diagnosed in February 2016 was treated with chemotherapy. He was followed classically with FDG PET/CT, which assessed the complete metabolic response in June 2016. In July 2016, he had autologous stem cell transplantation. Two months later, he underwent an FDG PET/CT for revaluation. It showed intense FDG uptake in the medullary canal from cervical 4 to thoracic 4, bilateral cervical 7 to thoracic 8, and right thoracic 9 to 12 nerve roots, leading to the diagnosis of neurolymphomatosis. A clinical cervical radiculopathy and spinal MRI results reinforced this diagnosis.